PENGGUNAAN METODE PEMBELAJARAN FIELD TRIP UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PGSD PADA MATA KULIAH PENDIDIKAN IPA KELAS TINGGI - Rupina Magdalena Br Tarigan (JURNAL TEMATIK, 2019)
This study aims to know the use of Field Trip learning methods to improvestudent learning outcomes in High Class Science courses. This type of research is ClassAction Research. The results of the study show that in the first cycle data obtained fromstudent learning outcomes in a classical still low, namely from 31 students there wereonly 3 people (9.68%) with very good learning outcomes, and 5 people (16.13%) withcategories good, 12 people (38.71%) in sufficient categories, while student learningoutcomes in the category of less than 11 people (35.48%). Then after the second cycle,with the application of the Field Trip learning method student learning outcomesincreased to 6 people (19.35%) with very good learning outcomes, 17 people (54.84%)with good categories, whereas with the category there were only 7 people (22.58%), butthere is still one person (3.23%) whose learning outcomes are still relatively poor. Basedon the results of testing hypotheses conducted by the researcher, conclusions wereobtained by using the Field Trip learning method that could improve the learningoutcomes of primary education students in the Quality University in the High ClassScience Education course.